Mass motorization + mass transit an American history and policy analysis - Jones, David W. (Indiana University Press, 2008)
Mass Motorization and Mass Transit examines how the United States became the world's most thoroughly motorized nation and why mass transit has been more displaced in the United States than in any other advanced industrial nation. The book's historical and international perspective provides a uniquely effective framework for understanding both the intensity of U.S. motorization and the difficulties the country will face in moderating its demands on the world's oil supply and reducing the CO2 emissions g
Keywords: Transportation, Automotive : United States : History; Transportation, Automotive : Government policy : United States : History